Collaborative Governance and the Urgency of Digitizing Public Services: Encouraging Licensing and Legalization of Local Businesses - Mutia, Ulmi Sri; Fatmawati; Mahsyar, Abdul (GoAcademica Research & Publishing, 2024)
This study aims to analyze licensing and local business legalization, collaborative governance, and simultaneous digitization of public services. This study takes a case study in Barru District, South Sulawesi. The reason for choosing this case study is because Barru Regency is one of the regencies that has implemented breakthrough innovations in the field of business licensing and has been recognized nationally. This research uses a qualitative approach by relying on online research methods (ORMs) to collect data and information through official government websites. The analysis tool used is Nvivo 12 Plus for data coding. The findings of this study indicate that the Government of Barru District has adopted the concept of collaborative governance and digitization of public services to encourage licensing and legalization of local businesses. It involves the involvement of local governments, the private sector and the general public in a more transparent, accountable and efficient licensing process and business management. The government has also explicitly set up a licensing agency to personally visit business actors. In addition, the government also initiated website-based digital services. The government's official website in Barru District has positively contributed to providing easy and fast access to public services, such as information on business licensing applications, investment opportunities, service standards, and sectoral data mapping. Complaint services and call centres are also available to assist the community in providing input and complaints related to public services regarding licensing and legalization of local businesses.